Analysis of corner kicks in FIFA 2018 World Cup - Zileli, R.; Söyler, M. (Journal of Human Sport & Exercise, 2022)
The aim of this study is to analyse the corner kicks taken in the matches played in the FIFA 2018 World Cup. A total of 606 corner kicks that were used in 64 matches in the competitions were analysed. The data were analysed in terms of the parameters of the direction in which the corner kick is taken (right, left), the time interval in which the corner kick is taken (1-15, 16-30, 31-45, 46-60, 61-75, 76-90), the region where the ball falls in the penalty area (1st, 2nd, 3rd, 4th, 5th, 6th.), the player whom the ball meets in the penalty area (goalkeeper, defender, striker), the body part which contacts the ball (head, foot, hand), attack result (goal, out, corner kick, clearing the ball, goalkeeping) and the body part with which the goals are scored (head, foot). The results indicated that in FIFA 2018 World Cup competitions, the right and left corner kicks were almost evenly distributed, but unlike previous matches, the corner kicks were taken from the left between the 16th and the 30th minutes, and from the right between the 61st and the 75th minutes. Contrary to the previous World Cups, it was found that fewer corner kicks were taken by spreading the game to both wings, the time interval changed in the search for goals from corner kicks, the target area was used predominantly, and the attacking players stood out compared to the defence players, and an equal number of goals were scored with the head and foot.